Some observations from PT Limbang Ganeca Forest Concession, East Kalimantan - Christian Gonner (KUKILA, 2000)
During July and August 1998 bird surveys were carried out in a forest concession near Belayan river at Limbang Ganeca. East Kalimantan. 166 species were found along five transects at 500 m, several logging roads and Sungai Ritan. The species list includes several threatened and rare species, such as Wallace's Hawkeagle Spizaetus nanus, Bornean Bristlehead Pityriasis gymnocephala, Malaysian Honeyguide Indicator archipelagus, Bomean Wrenbabbler Ptilocichla leucogrammica and Grey-breasted Babbler Malacopteron albogulare.